Exploring the phenomenon of triggering events for social justice educators - Obear, Kathryn Helen (ScholarWorks@UMass Amherst, 2000)
The quality of interactions between facilitators and groups is critical to the success of social justice educational experiences. Given the importance of these interpersonal dynamics, it is curious that there are few references and no research studies in the literature that explore the phenomenon of triggering events for facilitators and trainers of diversity awareness and social justice educational experiences. The results of this study will help to fill this gap in the social justice education literature by describing the types of situations in which educators feel triggered, the ways they respond to triggering events, and the core competencies and strategies that help educators use triggering events as “teachable moments” that further participant learning. I collected questionnaires from forty respondents and conducted in-depth interviews with fifteen educators from a range of social identities (race and gender), years of experience (6–35), and both formal academic and informal training settings. These educators reported experiencing a wide range of triggering events. They often felt overwhelmed, surprised, and “de-skilled” by the intensity of their emotional reactions and felt that they had responded to the situations in ways that were less effective. A core finding from this study identified the intervention strategies with which educators were satisfied, including using self-management strategies to re-establish a sense of emotional equilibrium, using the self as instrument to diagnose the situation and further participant learning, and engaging the resistance of participants to facilitate honest dialogue. Another critical finding identified ways in which intrapersonal issues and unresolved past traumas of educators appeared to influence how they appraised events as triggers and responded in the moment. Those educators who developed greater self-awareness and participated in personal healing work reported experiencing fewer triggering events and greater satisfaction with how they managed the ones they encountered. Data from this study will help coordinators of professional development programs for social justice educators provide opportunities to gain the competencies to manage emotional reactions and choose more effective interventions during triggering events. This study has implications for professional development programs in other helping professions including counseling, social work, health care, teaching, human resources, and organization development.